Effectiveness of endophytic bacteria for some medicinal plants as probiotics for Nile tilapia (Oreochromis niloticus) - Ali, Sayeda; Yones, Eman; El-badry, Hassan (Indonesian Aquaculture Journal, 2023)
The main objective of this research is to study the possibility of using endophytic bacteria isolated from some medicinal plants (onion, Allium cepa, brassicales, Salvadora persica, and fenugreek, Trigonella foenum-graecum) as probiotics for Nile tilapia (Oreochromis niloticus). Fish growth was evaluated using fish growth performance indices and approximate fish composition. Fish health was assessed by quantifying some biochemical compounds in fish serum, and at the end of the experiment, a challenge test was performed with Vibrio parahaemolyticus. The use of endophytic bacteria increased all indicators of growth performance compared to the control group. Endophytic bacteria of Fenugreek recorded higher growth performance than other plants. Moreover, in all treatments except for onion, bacteria mixed with feed significantly increased in fish growth performance compared to bacteria added to rearing water. Endophytic bacteria of onion and fenugreek recorded higher concentrations of protein in muscles than the control group by 56 and 49%, respectively. Furthermore, 88, 75 and 63% of the treatments recorded a decrease in albumin, ALT and AST concentration compared to the control group. Although the concentration of urea in the blood was higher than the control group by about 7.4 to 44.3%, but the challenge test showed that all treatments had a 20% mortality rate compared to the control group (10%). As a result, the endophytic bacteria of onion, brassicales and fenugreek can be used as probiotics for Nile tilapia. Further study is needed to elucidate the optimal bacterial concentration necessary for tilapia growth.